Urinary tract infection profile among a hospitalized newborn: a single center study in Iran, 2006-2015 (Faculty of Medicine Universitas Indonesia, 2018)
Background: Urinary tract infection in infants is associated with septicemia and genitourinary anomalies. This study was aimed at investigating the frequency, clinical signs, and anomalies in infants hospitalized for urinary tract infection.Methods: This cross-sectional study was conducted on all infants with urinary infection who were hospitalized in the neonatal ward of Beâsat Hospital from 2006 to 2015.Results: Of 79 infants with urinary infection, 62% were male and 87.3% were term infants. The mean age at admission was 16.62±7.17 days, and the mean weight was 3276±478.23 grams. The most frequent clinical sign and the most common pathogen reported were prolonged jaundice (62%) and Escherichia coli (69.6%), respectively. Of the samples, 93.7% were obtained by suprapubic aspiration, 23% had leukocytosis, and 2.5% had urosepsis. In urinalysis examination, 81% had pyuria and 19% had positive nitrate. Among 25.3% infants who had abnormal ultrasound findings, the most abnormal finding was mild bilateral hydronephrosis and 6.3% of the infants had abnormal voiding cystourethrogram (VCUG) in which vesicoureteral reflux was the most frequent finding.Conclusion: It showed that a prolonged jaundice in infants should be considered as a strong factor predicting urinary tract infection.